MULTI-AKAD DALAM PERSPEKTIF FIKIH DAN IMPLEMENTASINYA DI PERBANKAN SYARIAH - Alfin, Aidil (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2015)
Social changes have significant influence to the various sides of life, including financial transactions. Construction contract which previously only known one contract for one transaction (al-'uqud al-Basithah), now has grown to such an extent that in almost all the Shari'ah banking covenants built more than one contract for one-time transactions, for example Musharaka Mutanaqishah (merger between shirkah owned by Ijarah contract), Ijarah Muntahiy Bittamlik (merger between Ijarah contract and purchase) and Murabaha lil bi amir al-syira '(merging two sale and purchase agreement). In principle, the same legal origin of the hybrid contract with a single contract, it could be legitimate and can also be imperfect. Prohibition hybrid contract as the hadith of Abu Hurayrah is not absolute. During the merger agreement-contract does not contain ghahar / jahalah and does not lead to usury, the hybrid contract valid from the perspective of Islamic jurisprudence.